An Easy Mixed-Method Analysis Tool to Support Rural Development Strategy Decision-Making for Beekeeping - Silvia Novelli; Monica Vercelli; Chiara Ferracini (Land, 2021)
The EU has long-recognised the functions and contributions of beekeeping in sustainable rural area development. In 2018, the EU adopted the Pollinator Initiative to strengthen its pollinator conservation policies. To support the design of effective rural development actions, this work describes and tests an easy-to-apply, mixed-method tool for use with SWOT analysis. A two-step methodology was trialled with beekeepers in Piedmont Region (NW Italy). In step one, two independent groups of beekeepers operating in separate protected and intensive agricultural areas completed a SWOT matrix. In step two, three expert panels (beekeeper association leaders, honey market organisation leaders, and entomologists) prioritised the effects of the SWOT items with a quantitative weighting and rating process. Results suggest that the sector needs better-targeted incentives and that ‘soft’ policies on extension, advisory, and institutional measures could play a relevant role. The method was also confirmed as suitable for use with non-expert evaluators, such as policy officers and practitioners.